2019
DOI: 10.3390/pathogens8030121
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of Chikungunya Virus in Field-Caught Aedes aegypti Mosquitoes Collected during the Recent Outbreaks in 2019, Thailand

Abstract: Chikungunya virus (CHIKV) is a mosquito-borne virus belonging to the genus Alphavirus. The virus is transmitted to humans by the bite of infected female Aedes mosquitoes, primarily Aedes aegypti. CHIKV infection is spreading worldwide, and it periodically sparks new outbreaks. There are no specific drugs or effective vaccines against CHIKV. The interruption of pathogen transmission by mosquito control provides the only effective approach to the control of CHIKV infection. Many studies have shown that CHIKV can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 39 publications
(37 reference statements)
0
28
0
Order By: Relevance
“…Populations of Ae. aegypti males collected in Mexico [42] and Thailand [43] have also been identified to be naturally infected with CHIKV. It has been shown that the high vector competence of both Ae.…”
Section: Discussionmentioning
confidence: 99%
“…Populations of Ae. aegypti males collected in Mexico [42] and Thailand [43] have also been identified to be naturally infected with CHIKV. It has been shown that the high vector competence of both Ae.…”
Section: Discussionmentioning
confidence: 99%
“…aegypti vector [ 42 ]. The E1:A226V mutation of CHIKV is present in mosquitoes from Thailand: Ubon Ratchathani, Chiang Rai, Chiang Mai, Nakhon Sawan, and Songkha provinces, while the E1: K211E mutation is found in samples from Nong Khai, Bangkok, Prachuap Khiri Khan, and Krabi Province [ 40 ].…”
Section: Arboviruses and Vectors In Thailandmentioning
confidence: 99%
“…Both male and female Ae. aegypti were found to carry CHIKV (E1: A226V and E1: K211E) infection, with infection rates of 0.85% and 3.28%, respectively [ 40 ]. However, infection rates rely on several parameters, may change from one mosquito species to another, and depend on the viral dose, temperature, etc.…”
Section: Arboviruses and Vectors In Thailandmentioning
confidence: 99%
“…This mutation is associated with increased viral transmission in Aedes albopictus ( 5 ). The most recent CHIKV outbreak in Thailand was reported in 2018 to 2019 ( 6 , 7 ). To investigate the CHIKV genomes from this outbreak, we sequenced 22 existing CHIKV isolates from Thailand.…”
Section: Announcementmentioning
confidence: 99%